2020
DOI: 10.1093/rpd/ncaa026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Radiation Dose to the Hands of Orthopaedic Surgeons During Fluoroscopy Using Stored Images

Abstract: Data were collected from 642 orthopaedic interventions during which the images produced by X-rays were recorded. By examining these images, it is possible to determine the time that the orthopaedic surgeons’ hands were exposed to the direct radiation beam. The procedures with greater exposure to the direct beam were those involving the hand (median 15 s) and the wrist (median 13 s). Two surgeons wore a ring to measure the absorbed dose at the fingers: one on the dominant hand and the other on the non-dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As a result, the noise in the low-dose CT images was reduced. More than 90% of readers in a recent study [ 46 ] by Cross et al found that the quality of low-radiation-dose CT images, which were produced in part with the use of an artificial neural network (ANN), was equal to or greater than that of CT images obtained using standard radiation doses. This conclusion was reached based on the findings of the study that was conducted by Cross et al…”
Section: Image Acquisition and Reconstructionmentioning
confidence: 99%
“…As a result, the noise in the low-dose CT images was reduced. More than 90% of readers in a recent study [ 46 ] by Cross et al found that the quality of low-radiation-dose CT images, which were produced in part with the use of an artificial neural network (ANN), was equal to or greater than that of CT images obtained using standard radiation doses. This conclusion was reached based on the findings of the study that was conducted by Cross et al…”
Section: Image Acquisition and Reconstructionmentioning
confidence: 99%
“…1,2 The early diagnosis of heart disease is vital and is itself the most complicated task in the field of medical diagnosis. [3][4][5] All the above-specified factors are taken into consideration by the doctors at regular intervals of time while analyzing and understanding the health condition of the patient in manual check-ups. The discomfort felt by an individual is the major indicator of heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…The term heart disease relates to a “number of medical conditions related to the heart and all its parts.” The principal reasons for the increase in the expectancy rate of both men and women are due to the delay in the identification of the disease severity 1,2 . The early diagnosis of heart disease is vital and is itself the most complicated task in the field of medical diagnosis 3‐5 . All the above‐specified factors are taken into consideration by the doctors at regular intervals of time while analyzing and understanding the health condition of the patient in manual check‐ups.…”
Section: Introductionmentioning
confidence: 99%